Novel Technique for Detection of Wormhole Attack in MANET - Singh, Sukhwinder; Kansal, Rajnish (International Journal of Computer Sciences and Engineering, 2025)
The wireless nature of communication makes mobile ad hoc networks unreliable vulnerable to any attack with intent to steal the data can do so by deploying malicious nodes in the network. Normally the routing protocols are designed to find shortest path length is determined using hop count as metric. Out of many attacks the wormhole attack is pretty dangerous one as it is launched using two pairs of malicious nodes with create a tunnel by skipping few nodes in between source and destination node. The existing scheme considers the wormhole attacks when there are no intermediate nodes present between destinations. This technique is suitable for scenarios where the path length between source and destination is two hops only .this scheme cannot be used for networks with layer hops between source and destination node. In this research work, the novel scheme is proposed which detect and isolation malicious nodes from the MANETs. The malicious nodes are responsible to trigger wormhole attack in MANET. The proposed technique is implemented in NS2 and simulation results shows that proposed technique performs well as compared to other techniques